1986
DOI: 10.1126/science.3775367
|View full text |Cite
|
Sign up to set email alerts
|

Curvilinear, Three-Dimensional Motion of Chromatin Domains and Nucleoli in Neuronal Interphase Nuclei

Abstract: The term "nuclear rotation" refers to a motion of nucleoli within interphase nuclei of several cell types. No mechanism or function has been ascribed to this phenomenon, and it was unknown whether nuclear structures in addition to nucleoli participate in this motion. Moreover, it was unclear whether nuclear rotation occurs independent of concurrent motion of juxtanuclear cytoplasm. The work reported here presents quantitative evidence, for three-dimensional intranuclear, tandem motion of fluorescently labeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 22 publications
3
41
0
Order By: Relevance
“…A similar phenomenon has been reported a number of times during the past 60 or so years for cultured cells and some cells in the developing brain of the zebra fish embryos (Pomerat, 1953;Bard et al, 1985;De Boni and Mintz, 1986;Albrecht-Buehler, 1986 and1988;Herbomel, 1999). However, the mechanism and significance of nuclear wriggling remained unclear.…”
Section: Introductionsupporting
confidence: 74%
“…A similar phenomenon has been reported a number of times during the past 60 or so years for cultured cells and some cells in the developing brain of the zebra fish embryos (Pomerat, 1953;Bard et al, 1985;De Boni and Mintz, 1986;Albrecht-Buehler, 1986 and1988;Herbomel, 1999). However, the mechanism and significance of nuclear wriggling remained unclear.…”
Section: Introductionsupporting
confidence: 74%
“…8). Early studies tracking changes in location of large segments of chromatin and whole chromosome territories indicated that, when corrected for nuclear rotation, the regions were essentially immobile over distances .0.4 mm (Cremer et al 1982, Diboni and Mintz 1986, Shelby et al 1996. However, more recent work combining higher spatial resolution with in vivo labeling of smaller defined segments of chromatin, revealed a more complex scenario with different regions of chromatin showing very different mobilities.…”
Section: Chromatin Dynamicsmentioning
confidence: 99%
“…The as-325 sociation of nuclear reorganization with changes in cell function therefore suggests that spatial reorganization of chromatin domains may play a role in the control of gene expression. (De Boni and Mintz, 1986;De Boni, 1994).…”
Section: Introductionmentioning
confidence: 99%